2010 12th International Conference on Optimization of Electrical and Electronic Equipment 2010
DOI: 10.1109/optim.2010.5510545
|View full text |Cite
|
Sign up to set email alerts
|

Direct and post-discharges in environmental applications of cold plasmas

Abstract: Discharges in humid air are valuable tools for producing active species which react both at the liquid surface of the targets and in the solution. These species are responsible for a noticeable abatement of the pollutant concentration, even of recalcitrant compounds. The relevant kinetics are examined with special emphasis on Temporal Post Discharges Reactions which develop in the solution after the discharge is switched off and without supplying extra energy. The moieties responsible for this feature are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Recent studies have shown that nonthermal plasmas can be used to generate plasma-activated solutions with reactive oxygen species, reactive nitrogen species, and other species. In this study, we report dopamine polymerization happens in plasma-activated water (PAW) under acidic pHs (<5.5) and in the absence of oxygen.…”
Section: Introductionsupporting
confidence: 82%
“…Recent studies have shown that nonthermal plasmas can be used to generate plasma-activated solutions with reactive oxygen species, reactive nitrogen species, and other species. In this study, we report dopamine polymerization happens in plasma-activated water (PAW) under acidic pHs (<5.5) and in the absence of oxygen.…”
Section: Introductionsupporting
confidence: 82%
“…PAW generated by direct exposure to plasma jet has been attributed to causing a 5-log reduction of S. aureus ( Tian et al, 2015 ). Thus, the inactivation efficacy of PAW is comparable to chlorine-based sanitizers, but unlike chlorine-based sanitizers, PAW inactivation efficiency depends largely on nitrates, nitrites, and the presence of hydrogen peroxide ( Kamgang Youbi et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, long-lived ionized molecules in PAW include hydrogen peroxide ( H 2 O 2 ), nitrate ( NO 3 − ), nitrite ( NO 2 − ), and peroxynitrite ( ONOO − ) anions ( Tan and Karwe, 2021b ; Mizoi et al, 2022 ). Some studies have demonstrated that PAW can be used as a disinfectant to inactivate bacteria on contaminated solid surfaces or in liquids ( Kamgang Youbi et al, 2010 ; Joshi et al, 2018 ; Shah et al, 2023 ; Xu and Tan, 2023 ). PAW has been shown to damage bacterial membranes and penetrate the extracellular matrix ( Tian et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens can be easily inactivated by AOPs, particularly by ozone, hydrogen peroxide, OH radicals, H 2 O 2 , peroxynitrite, UV radiation, etc. Cells and spores inactivation mechanisms like direct destruction, volatization and etching of the cells, oxidative stress and nitrogen stress were extensively studied [23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%